Reviews of Environmental Contamination and Toxicology - Whitacre, David M. (Reviews of Environmental Contamination and Toxicology, Continuation of Residue Reviews, 2015)
Release, Transport and Toxicity of Engineered Nanoparticles Deepika Soni, Pravin K. Naoghare, Sivanesan Saravanadevi, Ram Avatar Pandey Source Characterization of Polycyclic Aromatic Hydrocarbons by using their Molecular Indices: An Overview of Possibilities Efstathios Stogiannidis, Remi Laane Respiratory and Cardiovascular Effects of Metals in Ambient Particulate Matter: A Critical Review Deborah L. Gray, Lance A. Wallace, Marielle C. Brinkman, Stephanie S. Buehler, Chris La Londe.